Studi Etika Bisnis Berdasarkan Alkitab - Philip Suciadi Chia; Juanda Juanda (Jurnal Teologi dan Pelayanan Kerusso, 2021)
Business ethics is part of special ethics (applied), which initially developed in the United States, where it highlights various moral aspects of human behavior that have professions in business and management. Studying business ethics can help people who are in the business world to be able to formulate and apply ethical principles in the economics and business world among each other. It is expected that ethical principles can help determining the right attitude in dealing with conflicts (both interests and conscience) that arise when doing business. Of course, the Bible will be a foundation (reference) in formulating ethical principles in business. Thus, this paper limits business ethics that only based on biblical truth, so that it does not open a space for business ethics based on the secular world. In addition, the writer will discuss the relationship between ethics and business, definition, various presuppositions in doing business, some examples of violations of business ethics and closed for the purpose of Bible-based business ethics. Abstrak Indonesia Etika bisnis merupakan bagian dari etika khusus (terapan), yang pada awalnya berkembang di Amerika Serikat, di mana menyoroti pelbagai segi moral perilaku manusia yang mempunyai profesi di bidang bisnis dan manajemen. Mempelajari etika bisnis dapat membantu mereka yang menggeluti dunia bisnis untuk dapat merumuskan serta menerapkan prinsip-prinsip etika dibidang ekonomi maupun dunia bisnis antar sesama. Prinsip-prinsip etika ini pun diharapkan dapat menolong dalam menentukan sikap yang benar dalam menghadapi konflik-konflik (baik kepentingan maupun hati nurani) yang timbul tatkala berbisnis. Tentu saja Alkitab akan menjadi landasan (acuan) dalam merumuskan prinsip-prinsip etika dalam berbisnis. Dengan demikian, tulisan ini membatasi etika bisnis hanya berdasarkan dari kebenaran Alkitab, sehingga tidak membuka ruang bagi etika bisnis menurut dunia sekuler. Di samping itu, penulis akan membahas mengenai kaitan antara etika dengan bisnis, definisi, berbagai presuposisi dalam berbisnis, beberapa contoh pelanggaran akan etika bisnis dan ditutup dengan tujuan etika bisnis yang berdasarkan Alkitab.